Master the electric pressure cooker : more than 100 delicious recipes from breakfast to dessert - Buttars, Marci; Graham, Cami (Skyhorse Publishing, 2017)
Learn to make a variety of recipes - from perfect grains and homemade yogurt to nutritious veggies and tender, fall-off-the-bone meats. Try over one hundred delicious recipes such as: Breakfast Peach Cobbler, Cinnamon Vanilla Applesauce, Mango Sunshine Jam, and Mexican Stuffed Bell Peppers with Chipotle Lime Sauce. In addition to yummy recipes, this cookbook will show you how to get familiar with your appliance, modify recipes, adjust cooking time, and troubleshoot common issues. Print run 50,000.